High frequencies of De Novo CNVs in bipolar disorder and schizophrenia - Malhotra, Dheeraj; McCarthy, Shane; Michaelson, Jacob J.; Vacic, Vladimir; Burdick, Katherine E.; Yoon, Seungtai; Cichon, Sven; Corvin, Aiden; Gary, Sydney; Gershon, Elliot S.; Gill, Michael; Karayiorgou, Maria; et al. (Neuron, 2011)
While it is known that rare copy-number variants (CNVs) contribute to risk for some neuropsychiatric disorders, the role of CNVs in bipolar disorder is unclear. Here, we reasoned that a contribution of CNVs to mood disorders might be most evident for de novo mutations. We performed a genome-wide analysis of de novo CNVs in a cohort of 788 trios. Diagnoses of offspring included bipolar disorder (n = 185), schizophrenia (n = 177), and healthy controls (n = 426). Frequencies of de novo CNVs were significantly higher in bipolar disorder as compared with controls (OR = 4.8 [1.4,16.0], p = 0.009). De novo CNVs were particularly enriched among cases with an age at onset younger than 18 (OR = 6.3 [1.7,22.6], p = 0.006). We also confirmed a significant enrichment of de novo CNVs in schizophrenia (OR = 5.0 [1.5,16.8], p = 0.007). Our results suggest that rare spontaneous mutations are an important contributor to risk for bipolar disorder and other major neuropsychiatric diseases.
Gesehen am 09.08.2022